ANALISIS SISTEM PENGENDALIAN INTERN PENJUALAN KREDIT PADA PT XYZ - Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2021)
ABSTRACTThis study aims to analyze the credit sales internal control system at PT XYZ. The research uses an approach approach, with the correlational method. The collection method is qualitative, in the form of primary and secondary data collected through documentation. The internal control system applied to PT XYZ is doing well, the shortcomings are still in the dual position, namely the dual position of the warehouse section with the shipping section, the accounting section with the current billing section. Billing delays are piled up containing the activity of the accounting function at the end of the period. There is no shipping section that can actually be separated from the warehouse, credit and billing sections, so it will be an obstacle in accountability. Keywords: Credit Sales System, Internal Control System.